Capital Control, Debt Financing and Innovative Activity - Dirk Czarnitzki; Kornelius Kraft (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2004)
The present paper first discusses theoretically the different incentives of manager- versus owner-controlled firms for investment into innovative activity. In addition, the role of debt financing is analyzed. Subsequently the results from an empirical study on the determinants of innovative activity measured by patent applications are presented. A sample of German firms covering 2,793 observations is used, and it turns out that companies with widely held capital stock are more active in innovation, i.e. weakly controlled managers show a higher innovation propensity. However, the higher the leverage the more disciplined the managers are.
Keywords: O31; L11; O32; C25; 330; Innovation; Patents; Corporate Governance; Limited Dependent Variables; Innovation; Betriebliche Investitionspolitik; Eigentümerstruktur; Fremdkapital; Patent; Schätzung; Corporate Governance; Deutschland